1999
DOI: 10.1002/(sici)1096-9861(19990607)408:3<437::aid-cne9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic cytomatrix protein Bassoon is localized at both excitatory and inhibitory synapses of rat brain

Abstract: Bassoon is a 420‐kDa protein specifically localized at the active zone of presynaptic nerve terminals. It is thought to be involved in the structural organization of the neurotransmitter release site. We studied the distribution of Bassoon transcripts and protein in rat brain and assessed which types of presynaptic terminals contain the protein. As shown by in situ hybridization, Bassoon transcripts are widely distributed in the brain and occur primarily in excitatory neurons. In addition, examples of γ‐aminob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 32 publications
4
72
0
4
Order By: Relevance
“…6 A, D, single arrowheads), as reported previously (Richter et al, 1999;Patrizi et al, 2008). However, no such clusters were found along AnkG ϩ portions of the AIS (Fig.…”
Section: Ais Portionsupporting
confidence: 82%
See 1 more Smart Citation
“…6 A, D, single arrowheads), as reported previously (Richter et al, 1999;Patrizi et al, 2008). However, no such clusters were found along AnkG ϩ portions of the AIS (Fig.…”
Section: Ais Portionsupporting
confidence: 82%
“…To clarify whether, and how, the molecular machinery for GABAergic transmission is organized in the pinceau formation, we investigated immunohistochemical localization of GAD, VIAAT, bassoon, NL2, and GABA A R␣1, because all are highly accumulated at GABAergic synapses on somatodendritic elements in PCs (Oertel et al, 1981;Fritschy and Mohler, 1995;Chaudhry et al, 1998;Richter et al, 1999;Varoqueaux et al, 2004). Our examination confirmed that these molecules were clustered at perisomatic sites of PCs, thus ensuring the specificity and sensitivity of the present immunohistochemistry.…”
Section: Discussionsupporting
confidence: 60%
“…To test whether SynGAP overexpression regulates synapses in general, we transfected cultured neurons with GFP-SynGAP and subsequently labeled neurons for Bassoon or NR1. Bassoon has been shown to be a component of nearly all synapses in the forebrain, rendering it an ideal marker for changes in synapse number (15). We observed no changes in total synaptic density or excitatory synapse number as measured by Bassoon and NMDA receptor immunolabeling (Fig.…”
Section: Syngap Regulates Synaptic Strength By Altering Ampar Trafficmentioning
confidence: 54%
“…These anatomical features sharply contrasted to those of the glutamatergic system; GluA2 subunit and mGluR5 were accumulated to the synaptic or perisynaptic membrane, respectively, facing glutamatergic terminals. Furthermore, prominent accumulation of Bassoon, one of the cytomatrix active zone (CAZ) proteins considered to act as a platform for active zone vesicles (Richter et al, 1999), was observed near the presynaptic membrane in glutamatergic terminals, whereas no such accumulation was discernible in cholinergic varicosities. This finding implies that the molecular machinery for ACh release is not integrated into a specific site of given varicosities, unlike the active zone at glutamatergic synapses.…”
Section: Is Scarce In Cortical Gabaergic Interneuronsmentioning
confidence: 99%